Parent-Child Conversations in the Perspective of Maqāṣidī Tafsir - Andri Gunawan; Siti Nur Riani; Siti Marhamah (SALAM: Jurnal Sosial dan Budaya Syar-i, 2026)
This article aims to analyze the concept of parent-child conversations in the Qur'an through the perspective of Maqāṣidī Tafsir (objectives-based Qur'anic exegesis). Family communication serves as a primary instrument in character formation, the transmission of religious values, and the development of a child's personality. The Qur'an presents various models of dialogue between parents and children, particularly in the narratives of Luqman and his son, Prophet Ibrahim and Prophet Ismail, as well as the family dialogues of Prophet Ya'qub. This study employs a qualitative library research method using a maqāṣidī exegetical approach. The analysis focuses on Qur'anic verses that contain parent-child conversations by exploring the higher objectives (maqāṣid) embedded within them. The findings reveal that parent-child conversations in the Qur'an are not merely a means of conveying messages; rather, they function as a strategic instrument for safeguarding religion (ḥifẓ al-dīn), preserving life (ḥifẓ al-nafs), protecting intellect (ḥifẓ al-‘aql), maintaining lineage (ḥifẓ al-nasl), and fostering social morality. Qur'anic dialogues demonstrate communication patterns that are rational, compassionate, participatory, and oriented toward the realization of human well-being (maṣlaḥah). The maqāṣidī approach shows that family communication in Islam constitutes an integral part of the effort to nurture generations who are faithful, morally upright, and socially responsible.